2019
DOI: 10.1016/j.jval.2018.07.875
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Response Burden Associated with Completion of Patient-Reported Outcome Assessments in Oncology

Abstract: Background: Patient response burden is often raised as a human subject concern in consideration of the length or complexity of patient-reported outcome (PRO) instruments used in oncology. Objectives: To quantify patient response burden and identify its predictive factors. Methods: Data were collected presurgically during a prospective trial that used a comprehensive symptom and healthrelated quality-of-life (HRQOL) PRO assessment. A subset of patients also completed HRQOL interviews. Response burden was captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 39 publications
1
47
0
1
Order By: Relevance
“…To the majority of participating women, the time to complete the questionnaires (mean 10 minutes) was acceptable, while patient burden was considered a potential barrier in advance. 20 Furthermore, most women were willing to participate at all timepoints in case of future implementation. However, as one-third of the women considered the timepoint just after birth (T3) too burdensome, the added value of timepoint T3 should be evaluated concisely.…”
Section: Discussionmentioning
confidence: 99%
“…To the majority of participating women, the time to complete the questionnaires (mean 10 minutes) was acceptable, while patient burden was considered a potential barrier in advance. 20 Furthermore, most women were willing to participate at all timepoints in case of future implementation. However, as one-third of the women considered the timepoint just after birth (T3) too burdensome, the added value of timepoint T3 should be evaluated concisely.…”
Section: Discussionmentioning
confidence: 99%
“…Patient burden is often raised as a concern regarding the inclusion of PRO instruments in oncology trials, however, in a study conducted by Atkinson et al patients who completed a lengthy battery of PRO assessments reported minimal response burden. 16 In fact, in that study 32% of participants indicated that they would have liked to report additional information. While the current data cannot directly address response burden of increased reporting, patient preference for episodic or daily reporting suggests that patients do not expect to be overwhelmed by such demands.…”
Section: Discussionmentioning
confidence: 88%
“…15 While preliminary evidence suggests that a relatively lengthy battery of PROs was not perceived by patients as significantly burdensome, it is unclear if patients would be willing to complete PRO measures with more frequency. 16 A first step toward clarifying optimal frequency of PRO reporting in oncology is to examine patient preference in reporting. To that end, the current study aimed to gain a better understanding of oncology patients' reporting preferences.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it will help to anticipate patients’ needs—according to the Institute of Medicine, patient-centered healthcare should be an integral part of the healthcare system [ 45 ]. Despite the potential response burden of completing such a measure in oncology trials, patients with cancer may not perceive the experience as overly burdensome [ 46 ].…”
Section: Discussionmentioning
confidence: 99%